Historical Antecedents and Contemporary Challenges of the Legislatures in Africa - (:unkn) unknown (My University, 2023)
The study investigated the historical roots of the underdevelopment of Africa’s representative institutions. Despite its global prevalence, the author noted that the legislature has been involved in struggles for political power and relevance across political systems. The worldwide resurgence of democracy with the attendant collapse of global communism in the last decade of the Twentieth Century has translated to increased visibility for the legislatures as many African dictatorships got swept away by the waves, forcing a return to democratic rule. But then, the democratic governments disproportionately weighed governmental powers in favour of the executive. The author considered how ‘Colonialism in Africa shapedAfrican history, in relation to the legislature. In many countries, the legislatures were part of the colonial governmental apparatus handed over at or before independence. In the circumstances, the workings and challenges of representative institutions in Africa had to be understood within the context of the historical forces that shaped and continued to shape their emergence and contemporary relevance. The author identified people-centred constitutional re-engineering, more proactive posture on the part of legislators themselves, and improved capacity-building supports tailored towards the needs and peculiarities of individual parliaments as the irreducible minimum for strengthening the legislatures and creating responsive and citizens-friendly environments for sustainable democracy and good governance in Africa.
Keywords: African Research